Implementation of BLT DD: Insights from Village Cash Assistance Program - Qomariyah, Nurul; Choiriyah, Ilmi Usrotin (Indonesian Journal of Cultural and Community Development, 2024)
Background: Direct Cash Assistance from village funds (BLT DD) is vital for supporting rural communities, particularly during economic challenges. Specific background: Since 2020, Desa Gelam has allocated funds for BLT DD, making it a relevant case for examining program implementation. Knowledge gap: Limited research exists on the detailed execution and impact of BLT DD at the village level. Aims: This study analyzes the implementation of BLT DD in Desa Gelam, focusing on the roles of village officials and the importance of standard operating procedures (SOPs) for transparency. Results: Findings reveal that clear SOPs enhance the effective distribution of aid, with significant contributions from the village head and welfare officer, aligning with Edward III’s theory of communication, resources, disposition, and bureaucratic structure. Novelty: This research offers insights into how structured procedures improve social aid program execution, emphasizing village leadership. Implications: The study highlights the necessity of clear guidelines and strong leadership to ensure successful social assistance programs like BLT DD, serving as a model for enhancing aid distribution efficiency in other villages. Highlights : Role of SOPs: Clear standard operating procedures enhance transparency and efficiency in aid distribution. Leadership Impact: Village head and welfare officer are crucial for the successful implementation of BLT DD. Theoretical Alignment: Findings support Edward III’s theory on effective communication and resource management in social programs. Keywords: Direct Cash Assistance, BLT DD, Desa Gelam, standard operating procedures, village leadership